Fertilization - Shalgi, Ruth (Henry Stewart Talks, 2019)
Sperm transport along the male tract, Sperm transport along the female tract, Capacitation and acrosome reaction, Transport of oocytes to the fertilization site, Penetration through the egg investments, Recognition, binding and fusion of sperm to the oocyte membrane, Activation of the oocyte and cortical reaction, Resumption of the second meiotic division, Pronuclear development and DNA replication, Sperm contribution to the developing embryo